THE EFFECT OF E-PROCUREMENT UTILIZATION, APPLICATION OF GOVERNMENT ACCOUNTING STANDARDS (SAP), AND APPLICATION OF INTERNAL CONTROL SYSTEM (SPI) ON THE QUALITY OF FINANCIAL REPORTS AT CLASS 1 AGRICULTURAL QUARANTINE CENTERS SEMARANG - Sukardi; Eddy Riyanto Oemar Husein; Ira Wardeni; Willia Octadina; Maisaro; Khairil; Indrayani; Muammar Khaddafi (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2023)
The quality of financial reports is the most important factor in government organizations such as the Class 1 Agricultural Quarantine Office in Semarang. This study aims to analyze the effect of e-procurement, the application of government accounting standards, and the internal control system for the quality of financial reports. The population in this study were all employees of the Class 1 Semarang Agricultural Quarantine Center with 110 employees. The number of samples in this study was 110 employees with the sampling method using the census. The data analysis method used is the path analysis model. The results of the research are the simultaneous effect of the use of e-procurement, the application of government accounting standards, and the internal control system together have a significant (0,000) and effect (122,450) on the quality of financial reports. The effect of the use of e-procurement, implementation of government accounting standards, and internal control systems on the quality of financial reports is 77%. The results of the partial hypothesis testing of the use of e-procurement have a positive (0,379) and significant (0,000) effect on the quality of financial reports. The application of government accounting standards has a positive (0,397) and significant (0,000) effect on the quality of financial statements. The internal control system has a positive (0,186) and significant (0,016) effect on the quality of financial statements.